(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
Antroponyms forming part of Ukrainian idioms are analysed in this article. Some of them sustain connection with specific historic personalities, others take the part of generalized names-testimonials of social, moral and priorities of the Ukrainians.